A robust all-inorganic hybrid energy harvester for synergistic energy collection from sunlight and raindrops. (24th November 2020) - Liu, Xiaolan; Cui, Peng; Wang, Jingjing; Shang, Wanyu; Zhang, Song; Guo, Junmeng; Gu, Guangqin; Zhang, Bao; Cheng, Gang; Du, Zuliang
Abstract: As a new concept of the device, a hybrid energy harvester integrated with a water droplet triboelectric nanogenerator (WD-TENG) and a solar cell has been reported to convert raindrop energy and solar energy into electricity. However, organic triboelectric layers are usually utilized in previous studies that might be decomposed under long-term UV irradiation, resulting in degradation of the hybrid energy harvester. In this work, a fully inorganic hybrid energy harvester is demonstrated. Superhydrophobic SiO2 film is introduced to the system as both the triboelectric layer of the WD-TENG and the anti-reflective layer of the solar cell, which could increase the power conversion efficiency (PCE) of the solar cell from 15.17% to 15.71%. Meanwhile, WD-TENG with the SiO2 triboelectric layer could collect energies from rain droplets. This superhydrophobic SiO2 film could effectively reduce the dependence of the tilt angle for the WD-TENG and bring up self-cleaning performance for the hybrid energy harvester. Moreover, this fully inorganic architecture could enhance the stability of the hybrid energy harvester, making it a promising strategy in practical applications.